The significance of leaf morphological characters for the identification of carica papaya L. cultivars in Malaysia - Chan , Lai Keng; Chris , K.H. Teo (Universiti Kebangsaan Malaysia, 2000)
The detailed study of the papaya leaves morphology indicated that there were significant differences in the macrostructures and microstructures of the leaves between the 22 papaya cultivars that were grown in Malaysia. The number of leaf main veins, number of lobes at the leaf margin, leaf shape, type of stomata and wax structures on the leaf surface, and the colour of leaf petiole were the important characters used for the identification of the papaya cultivars. This information enabled us to identify the 22 papaya cultivars grown in Malaysia with a proposed taxonomic key.